The Price of Delay: Supply Chain Disruptions and Pricing Dynamics - Salome Baslandze; Simon Fuchs (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study the role of supply chain disruptions in shaping consumer prices, focusing on both firms' own import shocks and strategic responses to competitors' disruptions. Using a newly constructed micro-level dataset that links transaction-level U.S. import data from Bills of Lading with high-frequency consumer prices and sales from a consumer panel, we develop a novel approach to estimate the price effects of cost shocks and product availability. Motivated by a model of delivery delays, cost shocks, and firm pricing, we implement a shift-share identification strategy based on delivery shortfalls, port congestion, and freight and import costs. We find sizable pass-through elasticities: firms raise prices in response to higher import costs and delivery delays, especially when disruptions persist. We also identify strategic pricing: firms–including non-importers–increase prices in response to competitors' supply chain disruptions. Using our estimates and back-of-the-envelope calculations from the model, we show that strategic interactions significantly amplified the direct effects of supply chain shocks on consumer prices during the pandemic.
Keywords: E31; F14; 330; supply chains; inflation; delivery delays; strategic interactions; pass-through; inventory